1991
DOI: 10.1007/bf00179706
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic fractures of long bones

Abstract: Forty-two patients with a total of 52 metastatic fractures of long bones were analysed retrospectively with regard to the type of treatment, complications, general mobility and survival. Endoprosthetic replacement appeared to be better than osteosynthesis in the proximal femur, and this method should also be considered in pathological fractures of the distal femur. Nailing is indicated in fractures of the shafts of long bones in the lower limb, and also in the humerus. Osteosynthesis with a plate has only limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…The long-term survival of patients after their first pathological fracture of a long bone has more than tripled for the most common cancers during the past 25 years, 8,21 and survival in our study was high compared with those undertaken in the 1970s and 1980s. 14,19,[22][23][24][25][26][27][28][29] In two Swedish studies which described patients treated surgically between 1986 and 1995, the one-year survival rate (0.3) was in the same range as that for three years in our group. 30,31 In many studies, patients with solitary bony metastases survived significantly longer than those with multiple lesions.…”
Section: Discussionmentioning
confidence: 84%
“…The long-term survival of patients after their first pathological fracture of a long bone has more than tripled for the most common cancers during the past 25 years, 8,21 and survival in our study was high compared with those undertaken in the 1970s and 1980s. 14,19,[22][23][24][25][26][27][28][29] In two Swedish studies which described patients treated surgically between 1986 and 1995, the one-year survival rate (0.3) was in the same range as that for three years in our group. 30,31 In many studies, patients with solitary bony metastases survived significantly longer than those with multiple lesions.…”
Section: Discussionmentioning
confidence: 84%
“…We used cement in conjunction with rod fixation for a number of reasons. These included strengthening the residual bone, enhancing fixation of the rod along its whole length not just at its ends, thus providing rotational stability [ 8 , 11 , 12 ], and also for the thermonecrotic effect of cement on tumor cells as the cement cures [ 11 ]. The need for cross bolting is obviated, minimizing the creation of new defects and thus weaknesses in the remaining bone.…”
Section: Discussionmentioning
confidence: 99%
“…We believe however that cement, used mostly with plates (seven out of eight plates and two out of 10 IM nails) has an important role in minimizing fixation failure. This goes along with many other studies that showed benefits to cementing [18,[21][22][23][24]. In Table 2, we listed the publications and patient's characteristics on metastatic humeral fractures available in the literature.…”
Section: Discussionmentioning
confidence: 97%